THE PERFORMANCE OF JUICER MACHINE ON VEGETABLE MILK PRODUCTION FOR SMALL AND MEDIUM INDUSTRIES - Uli Karyani; Panut Mulyono; I Made Miasa (Master in Systems Engineering, 2015)
The purpose of this research is to make juicer machine to produce vegetable milk for small and medium-scale industries, and the machine has been able to be made with a juicer machine dimensions 90 cm X 40 cm X 114 cm. With ½ HP motor power and motor speed 1420 r / min so as to grind soy beans, green beans and corn with a production capacity of each of the milk is on average 15 liters, 12 liters and 12 liters.The first study is to design and create a juicer machine to produce vegetable milk based soy bean, green beans and corn by using some filter size is 60 mesh, 80 mesh and 100 mesh to obtain a best filter size for each type of vegetable milk. And organoleptic test to determine the level of preference for vegetable milk and obtained the most preferred type of vegetable milk is soy milk with a 100 mesh filter.Anti-E.coli test result on vegetable milk as product quality standards, not found any E. coli in each sample tested. While the feasibility of vegetable milk production using a juicer machine is feasible to use in the business of making the three types of vegetable milk because it can give the advantage of 1.20-fold for each unit of the issued capital, the benefits outweigh the effort of making industrial scale vegetable milk usual household. And in terms of the market, producing vegetable milk is still a promising business seen from vegetable milk organoleptic test average of 60% is still loved and considers it important to consume vegetable milk.